Pemberdayaan Masyarakat Melalui Pembentukan Dan Pelatihan Kelompok Cegah Stunting (Centing ) Dalam Upaya Percepatan Penurunan Stunting Di Nagari Padang Laweh Kecamatan Sungai Pua Kabupaten Agam - Lili Dariani; Sefrina, Yosi; Bachtar, Fitrina (LPPM UMRI, 2023)
Indonesia faces nutritional problems which have a serious impact on the quality of human resources (HR). One of the problems of malnutrition that is still quite high in Indonesia is stunting. The results of the 2021 Indonesian Toddler Nutritional Status Study (SSGI), the national stunting rate fell by 1.6 percent per year. Based on data from the Sungai Pua Community Health Center regarding the recapitulation of nutritional status of toddlers (TB/U) in measurements in February 2022, the data on stunting incidence was obtained as follows: Nagari Batu Palano (13%), Nagari Padang Laweh (20%), Nagari Batagak (15%) , Nagari Sariak (12.3 %), Nagari Sungai Pua 9.23 %. Based on the data above, the Padang Laweh village is the village with the highest incidence of stunting and there is no group that cares about stunting. One of the problem solving efforts carried out in community service activities is to increase the human resource capacity of groups concerned with stunting prevention through structured formation and training activities. The targets for this activity are teenagers and elements of society who have been selected by providing material by resource persons using the lecture, question and answer method.